Cesium-silver-iodine thermal insulation material with ultralow thermal conductivity as well as preparation method and application of cesium-silver-iodine thermal insulation material

By developing cesium silver-iodine ternary metal halide CsAg2I3 insulating material, using its polycrystalline and single crystal states, ultra-low thermal conductivity and high thermal insulation performance are achieved, solving the problem of insufficient thermal conductivity of existing thermal insulation materials and expanding its application range.

CN119683673APending Publication Date: 2025-03-25TONGJI UNIV
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411586052.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The thermal conductivity of existing thermal insulation materials has not yet reached the target of less than 0.2W/m-K, limiting their application range.

Method used

A thermal insulation material of cesium silver iodine ternary metal halide CsAg2I3 was developed to achieve ultra-low thermal conductivity through the aggregation state of polycrystalline and singlecrystalline state. The thermal conductivity of the polycrystalline state is 0.09 W/m-K, and the thermal conductivity of the singlecrystalline state is 0.08-0.15 W/m-K, and it has anisotropy.

Benefits of technology

It achieves ultra-low thermal conductivity and improves thermal insulation performance. It is suitable for experimental-grade equipment thermal shielding, building insulation materials or daily thermal insulation and protective products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119683673A_ABST
    Figure CN119683673A_ABST
Patent Text Reader

Abstract

The invention relates to a cesium-silver-iodine thermal insulation material with ultralow thermal conductivity and a preparation method and application thereof. The chemical formula of the material is CsAg2I3. Comprising two aggregation states, namely a polycrystalline state and a single crystal state. The preparation method of the polycrystalline cesium-silver-iodine heat insulation material comprises the following steps: by taking binary iodide as a raw material, carrying out vacuum packaging, melting reaction quenching and heat treatment quenching, grinding into powder, carrying out vacuum high-temperature hot pressed sintering, and cooling to obtain a compact block material, namely the polycrystalline cesium-silver-iodine heat insulation material. According to the preparation method of the single-crystal-state cesium-silver-iodine heat insulation material, binary iodide serves as a raw material, and the single-crystal-state cesium-silver-iodine heat insulation material is obtained after vacuum packaging, melting reaction furnace cooling, slow cooling, nucleation and crystallization. Compared with the prior art, the cesium-silver-iodine thermal insulation material with ultralow thermal conductivity is prepared, a method for preparing a high-density and high-thermal-insulation material is explored, and the cesium-silver-iodine thermal insulation material has extremely low thermal conductivity (0.09 W / m-K of polycrystal and 0.08 W / m-K of single crystal) at the room temperature of 300K, and is a kind of thermal insulation material with great potential.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of new energy materials, and in particular to a cesium silver iodine thermal insulation material with ultra-low thermal conductivity, and a preparation method and application thereof. Background Art

[0002] In recent years, with the increasing demand for energy conservation, emission reduction and efficient energy utilization, the research and application of thermal insulation materials as a type of material used to reduce heat transfer has been significantly developed. Including building energy conservation, industrial system insulation, transportation insulation, etc., thermal insulation materials are of great significance for improving energy utilization efficiency, reducing energy consumption and reducing greenhouse gas emissions.

[0003] The heat transfer properties of materials are usually measured by thermal conductivity k. The thermal conductivity of a material usually consists of two parts: k = k e +k L , where k e is the electronic thermal conductivity, mainly contributed by electrons; k L is the lattice thermal conductivity, which is mainly contributed by lattice vibration. The insulation material is usually selected as an electrical insulating material so that the contribution of electrons to heat conduction can be almost ignored. Determined by, where C v is the specific heat, v g is the phonon group velocity, and τ is the phonon relaxation time. On the one hand, the lattice thermal conductivity of known materials can be reduced by introducing lattice defects of various dimensions or increasing lattice anharmonic vibrations; on the other hand, materials with complex lattice structures, large molar masses, and lattice distortion usually have intrinsically low lattice thermal conductivity, which has become one of the main research directions for the development of new materials with intrinsic ultra-low thermal conductivity.

[0004] Ternary metal halides are a class of materials with broad application prospects in the field of optoelectronics, and their compound types and ratios are rich and varied. Due to its complex chemical composition and crystal structure, the intrinsic low lattice thermal conductivity of this type of material has received widespread attention in recent years. It has been reported in the literature that ternary metal halides such as Cs3Bi2I9, Cs2SnI6 and CsPbI3 have extremely low thermal conductivity (about 0.2-0.4W / mK), and are a class of thermal insulation materials with great potential.

[0005] So far, the thermal conductivity of cesium silver iodine ternary metal halide has not been studied, and dense insulation materials with thermal conductivity lower than 0.2 W / mK have not been discovered, which limits the application range of insulation materials. Summary of the invention

[0006] The purpose of the present invention is to overcome the defects of the above-mentioned prior art and provide a cesium silver iodine insulation material with ultra-low thermal conductivity and a preparation method and application thereof.

[0007] The purpose of the present invention can be achieved by the following technical solutions:

[0008] One of the technical solutions of the present invention provides a cesium silver iodine thermal insulation material with ultra-low thermal conductivity, whose chemical formula is CsAg2I3; the cesium silver iodine thermal insulation material includes two aggregation states, namely, polycrystalline cesium silver iodine thermal insulation material and single crystalline cesium silver iodine thermal insulation material.

[0009] Furthermore, the cesium silver iodine thermal insulation material has ultra-low thermal conductivity; the thermal conductivity of the polycrystalline cesium silver iodine thermal insulation material is 0.09 W / mK; the thermal conductivity of the single-crystalline cesium silver iodine thermal insulation material is anisotropic, and its thermal conductivity in the a-axis single crystal orientation, the b-axis single crystal orientation, or the c-axis single crystal orientation is different, and its thermal conductivity is 0.08-0.15 W / mK.

[0010] Furthermore, the thermal conductivity of the single-crystalline cesium silver iodine thermal insulation material with a-axis single crystal orientation is 0.08 W / mK.

[0011] Furthermore, the density of the polycrystalline and single-crystalline cesium silver iodine thermal insulation materials measured by the Archimedean method is about 4.6-5.1 g / cm 3 According to the lattice structure information, the theoretical density is calculated to be 5.11 g / cm 3 The density of polycrystalline and single crystalline cesium silver iodine insulation materials is about 90-100%.

[0012] Preferably, in some specific embodiments of the present application, the polycrystalline and single-crystalline cesium silver iodine thermal insulation materials have a density of 5.0 to 5.1 g / cm2 as measured by the Archimedean method. 3 According to the lattice structure information, the theoretical density is calculated to be 5.11 g / cm 3 The density of polycrystalline and single-crystalline cesium silver iodine insulation materials can be above 97%.

[0013] A second technical solution of the present invention provides a method for preparing a polycrystalline cesium silver iodine thermal insulation material, comprising the following steps:

[0014] (1) Vacuum packaging: the raw materials cesium iodide CsI and silver iodide AgI are mixed evenly and then vacuum packaged in a quartz tube;

[0015] (2) Melt reaction quenching: The quartz tube is heated to allow the raw materials to react in a molten state, and then the furnace is stopped and cooled to a certain temperature, and then quenched and cooled to obtain the first ingot;

[0016] (3) Heat treatment and quenching: the first ingot is vacuum-sealed in a quartz tube, heat-treated, and then quenched and cooled to obtain a second ingot;

[0017] (4) Pressure sintering: The second ingot is ground into powder, placed in a mold, and subjected to vacuum high-temperature hot-pressing sintering. The dense block material obtained after cooling is the polycrystalline cesium silver iodine thermal insulation material.

[0018] Furthermore, in step (1), the molar ratio of the raw materials cesium iodide CsI and silver iodide AgI is 1:2; the purity of the raw materials is greater than 99.9%;

[0019] Furthermore, the heating in step (2) is: heating the quartz tube from room temperature to 973-1173K at a rate of 140-180K / h and keeping it warm for 1-3h, so that the raw materials react in a molten state; and the shutdown cooling is to cool the quartz tube from 973-1173K to 523-723K at a rate of 100-120K / h.

[0020] Preferably, in step (2), the temperature of the quartz tube is raised from room temperature to 1073 K, so that the raw materials react in a molten state, and then the temperature of the quartz tube is lowered from 1073 K to 623 K, and then quenched and cooled.

[0021] Furthermore, the heat treatment in step (3) is: heating the quartz tube from room temperature to 373-473K at a rate of 40-80K / h and keeping the temperature for 1-3 days.

[0022] Preferably, in step (3), the quartz tube is heated from room temperature to 423K and kept at this temperature for 2 days for heat treatment.

[0023] Preferably, in step (4), the mold is a graphite mold.

[0024] Furthermore, in step (4), the vacuum high-temperature hot-pressing sintering adopts induction heating, the temperature is raised to 373-423K at a rate of 40-60K / min, the pressure is adjusted to 40-50MPa, and the temperature and pressure are kept constant for 5-15min; the cooling rate is 5-15K / min.

[0025] Preferably, in step (4), the sintering temperature is 393K, the sintering pressure is 45MPa, and the constant temperature and pressure treatment is carried out for 10 minutes, vacuum high-temperature hot pressing sintering is performed, and then slowly cooled to room temperature at a rate of 10K / min to obtain a polycrystalline cesium silver iodine insulation material.

[0026] Preferably, the absolute vacuum degree of the vacuum in step (1), step (3) or step (4) is not greater than 10 -1 Pa.

[0027] A third technical solution of the present invention provides a method for preparing a single-crystalline cesium silver iodine thermal insulation material, comprising the following steps:

[0028] (1) Vacuum packaging: the raw materials cesium iodide CsI and silver iodide AgI are mixed evenly and then vacuum packaged in a quartz tube;

[0029] (2) Melting reaction furnace cooling: The quartz tube is heated to allow the raw materials to react in a molten state, and then the furnace is stopped and cooled to obtain a polycrystalline first ingot;

[0030] (3) Single crystal growth: vacuum-packing the first polycrystalline ingot in a quartz tube, placing the quartz tube in a furnace and heating it, cooling it to room temperature after it is completely melted, so that the compound solidifies and crystallizes from the molten state, thereby obtaining the single crystal cesium silver iodine thermal insulation material.

[0031] Furthermore, in step (1), the molar ratio of the raw materials cesium iodide CsI and silver iodide AgI is 1:2; the purity of the raw materials is greater than 99.9%;

[0032] Furthermore, the heating in step (2) is: heating the quartz tube from room temperature to 973-1173K at a rate of 140-180K / h and keeping it warm for 1-3h, so that the raw materials react in a molten state; the shutdown cooling is: cooling the quartz tube from 973-1173K to room temperature at a rate of 100-120K / h.

[0033] Preferably, in step (2), the temperature of the quartz tube is raised from room temperature to 1073 K, the raw materials are allowed to react in a molten state, and then the temperature of the quartz tube is lowered from 1073 K to room temperature.

[0034] Preferably, the furnace body in step (3) is a furnace body having a temperature gradient of 10 to 20 K / cm;

[0035] Furthermore, in step (3), the heating is controlled by the tip of a quartz tube, the temperature is raised from room temperature to 453-513K at a rate of 40-80K / h and kept at that temperature for 1-3h; and the cooling is lowered to room temperature at a rate of 0.5-1K / h.

[0036] Preferably, the furnace body in step (3) is a furnace body with a temperature gradient of about 15K / cm, and the temperature is raised from room temperature to 483K at a rate of 60K / h in the furnace body, and after being completely melted, it is cooled to room temperature at a rate of 0.7K / h, so that the compound slowly solidifies and crystallizes from the molten state to obtain a single crystal cesium silver iodine insulation material.

[0037] Preferably, the absolute vacuum degree of the vacuum in step (1) and step (3) is not greater than 10 -1 Pa.

[0038] A fourth technical solution of the present invention provides an application of a cesium silver iodine insulation material with ultra-low thermal conductivity prepared by the above technical solution; the cesium silver iodine insulation material with ultra-low thermal conductivity is used to prepare thermal shielding covers for experimental-grade equipment, building insulation materials or thermal insulation and protective products for daily use.

[0039] Compared with the prior art, the present invention has the following beneficial effects:

[0040] (1) The present application explores and optimizes the conditions of raw material melting-heat treatment-high temperature hot pressing to obtain a CsAg2I3 dense bulk material with ultra-low thermal conductivity and high thermal insulation performance, namely the cesium silver iodine thermal insulation material. The polycrystalline cesium silver iodine thermal insulation material has low anisotropic thermal conductivity and good thermal insulation performance; the single-crystalline cesium silver iodine thermal insulation material is obtained by growing a single crystal to obtain anisotropic thermal conductivity, and its a-axis orientation has a thermal conductivity of κ~0.08W / mK at room temperature, which is lower than the b-axis orientation and the c-axis orientation.

[0041] (2) Under the preparation conditions described in the present invention, CsAg2I3 thermal insulation materials with high density and high thermal insulation performance can be prepared. CsAg2I3 materials have ultra-low frequency optical branches of characteristic vibration modes, resulting in very low sound speeds, and have strong lattice anharmonicity, so they have extremely low thermal conductivity (<0.3W / mK) over the entire temperature range. The thermal conductivity of polycrystalline CsAg2I3 at room temperature is κ~0.09W / mK, and the thermal conductivity of single-crystalline a-axis oriented CsAg2I3 at room temperature is κ~0.08W / mK, which is a class of highly potential thermal insulation materials.

[0042] (3) The present invention explores the preparation method of CsAg2I3 polycrystalline and single crystal bulk materials, and obtains high-density polycrystalline and single crystal bulk materials by exploring and optimizing the raw material melting-heat treatment-high temperature hot pressing conditions and the raw material melting-single crystal growth conditions. This preparation method has guiding significance for developing new insulating ternary metal halides, exploring the intrinsic mechanism of ultra-low thermal conductivity, and in-depth research on thermal properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 Phase analysis of polycrystalline and single-crystalline CsAg2I3 thermal insulation materials; the marks in the figure indicate: (a) powder X-ray diffraction pattern of polycrystalline CsAg2I3 changing with temperature, (b) lattice parameters of polycrystalline CsAg2I3 changing with temperature, (c) X-ray diffraction pattern of CsAg2I3 single crystal (100) / (010) / (001) plane, (d) SEM and EDS images of CsAg2I3 single crystal (100) / (010) / (001) surface;

[0044] Figure 2The relationship between thermal conductivity and temperature of polycrystalline CsAg2I3 thermal insulation material and single crystal CsAg2I3 thermal insulation material along different crystal axes;

[0045] Figure 3 (a) is a three-dimensional X-ray diffuse scattering stacking diagram of single-crystalline CsAg2I3 thermal insulation material at room temperature on the Q=(HKL) plane, and (b) is the mean square displacement of each atom in the three crystal axis directions calculated by single crystal X-ray diffraction refinement and AIMD simulation;

[0046] Figure 4 (a) is the transverse and longitudinal sound velocity measured along different crystal axes of single-crystalline CsAg2I3 insulation material at room temperature, and (b) is the transverse and longitudinal sound velocity Raman spectrum measured along different crystal axes of polycrystalline CsAg2I3 insulation material at room temperature. DETAILED DESCRIPTION

[0047] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is described in detail below in conjunction with specific embodiments. It should be noted that the following embodiments will help those skilled in the art to further understand the present invention, but do not limit the present invention in any form. It should be noted that for those of ordinary skill in the art, several variations and improvements can also be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.

[0048] All raw materials of the present invention have no particular limitation on their sources, and can be purchased from the market or prepared according to conventional methods known to those skilled in the art.

[0049] Example 1 A polycrystalline cesium silver iodine thermal insulation material

[0050] This embodiment provides a polycrystalline cesium silver iodine thermal insulation material (i.e., polycrystalline CsAg2I3 thermal insulation material), the chemical formula of which is CsAg2I3, and the preparation method is as follows:

[0051] (1) According to the chemical formula, binary compound powder raw materials cesium iodide CsI and silver iodide AgI with a purity greater than 99.9% are weighed according to the stoichiometric ratio of the composition CsAg2I3, mixed evenly and placed in a quartz tube, and the quartz tube is sealed under vacuum.

[0052] (2) The quartz tube containing the raw materials is suspended in a high-temperature muffle furnace, and the temperature is slowly raised to 1073 K at a rate of 160 K / h, and kept at 1073 K for 2 h, and then cooled to 623 K at a rate of 110 K / h, and then quenched to obtain the first ingot.

[0053] (3) The first ingot obtained in step (2) after high-temperature melt quenching is heat treated by slowly heating the temperature to 423 K at a rate of 60 K / h, keeping the temperature for 2 days, and then rapidly quenching and cooling to obtain a second ingot.

[0054] (4) Grinding the second ingot obtained in step (3) into powder, placing the powder in a graphite mold, using induction heating, heating to 393K at a rate of 50K / min, adjusting the pressure to 45MPa, and keeping the temperature constant for 10min, performing vacuum high-temperature hot pressing sintering, and then slowly cooling to room temperature at a rate of 10K / min to obtain a polycrystalline cesium silver iodine insulation material.

[0055] Example 2 A single crystal cesium silver iodine insulation material

[0056] This embodiment provides a dense single-crystalline cesium silver iodine thermal insulation material with anisotropic thermal conductivity in different crystal axis orientations, namely, CsAg2I3 single crystal bulk material / single-crystalline CsAg2I3 thermal insulation material / CsAg2I3 single crystal, and the specific method is as follows:

[0057] (1) The same as step (1) in Example 1;

[0058] (2) The quartz tube containing the raw materials in step (1) is suspended in a high-temperature muffle furnace, and the temperature is slowly raised to 1073 K at a rate of 160 K / h, kept at 1073 K for 2 h, and then cooled to room temperature at a rate of 110 K / h to obtain a first ingot.

[0059] (3) The first ingot obtained in step (2) after cooling in the high-temperature melting furnace is placed in a furnace body with a temperature gradient of 15 K / cm, and the temperature is controlled by the tip of a quartz tube. The temperature is raised from room temperature to 483 K at a rate of 60 K / h and kept at this temperature for 2 hours. After the ingot is completely melted, the temperature is lowered to room temperature at a rate of about 0.7 K / h, so that the compound slowly solidifies and crystallizes from the molten state, thereby obtaining the single crystal cesium silver iodine thermal insulation material.

[0060] The single-crystalline cesium silver iodine thermal insulation material obtained in step (3) can be subjected to directional grinding to obtain a single-crystalline bulk material with three crystal axis orientations of a-axis, b-axis and c-axis.

[0061] Example 3

[0062] The physical phase and thermal properties of the polycrystalline and single crystalline CsAg2I3 thermal insulation materials prepared in Example 1 and Example 2 are analyzed as follows: Figures 1 to 4 The experimental methods and steps are as follows:

[0063] (a) X-ray diffraction:

[0064] In order to determine the material structure of the synthesized single-crystalline CsAg2I3 thermal insulation material, a single crystal X-ray diffractometer (Bruker D8 VENTURE diffractometer, equipped with PHOTON IICCD detector, Mo-Kα radiation) was used to collect single crystal diffraction patterns. Each spot in the diffraction pattern corresponds to a specific arrangement of atomic planes in the crystal. The Bragg law (nλ = 2dsinθ) is then used to determine the interplanar spacing (d) and interplanar angle (θ) of the crystal. Subsequently, the structure refinement software SHELXT and OLEX are used to determine the position of atoms in the unit cell. Through an iterative process, the parameters such as atomic coordinates, unit cell parameters and temperature factors are optimized to best fit the experimental data. Finally, the crystal structure of the CsAg2I3 thermal insulation material is obtained, including atomic coordinates, unit cell parameters and atomic vibration displacements. Furthermore, according to the Bragg law (nλ = 2dsinθ), the crystallography software VESTA can be used to simulate the XRD diffraction pattern of the CsAg2I3 thermal insulation material.

[0065] In order to determine the phase composition of the synthesized polycrystalline CsAg2I3 thermal insulation material and whether the phase changes with temperature, an X-ray diffractometer equipped with Cu-Kα radiation (SmartLab, a multifunctional X-ray diffractometer produced by Rigaku Corporation) was used to scan in the range of 300 to 410K and 5 to 90°. The obtained X-ray diffraction peak data was compared with the simulated XRD diffraction pattern of the CsAg2I3 thermal insulation material mentioned earlier in this example, and it was confirmed that the polycrystalline phase was CsAg2I3.

[0066] Furthermore, all spectra from 300K to 410K were refined using the XRD spectrum refinement software GSAS-Ⅱ. According to the Bragg law (nλ=2dsinθ), the lattice constant of the polycrystalline CsAg2I3 insulating material at each temperature can be obtained. Taking the lattice constant at 300K as a reference, the thermal expansion coefficient α of each crystal axis can be calculated according to α=Δl / ΔT (where Δl is the length difference and ΔT is the temperature difference).

[0067] In order to orient the three crystal axis directions of the single-crystalline CsAg2I3 thermal insulation material, an X-ray diffractometer equipped with Cu-Kα radiation (Danfang circular X-ray diffractometer DX 2000) was used to scan in the range of 10 to 90°. The cleavage surface XRD diffraction pattern was obtained and compared with the simulated XRD diffraction pattern of the CsAg2I3 thermal insulation material mentioned earlier in this example to confirm the corresponding crystal plane, and then the (100) / (010) / (001) crystal plane was ground out according to the crystal structure of the CsAg2I3 thermal insulation material and the relationship between the crystal planes.

[0068] (ii) SEM and EDS images:

[0069] In order to determine the phase purity of the single crystalline CsAg2I3 thermal insulation material, a Phenom Pro desktop scanning electron microscope (SEM, Phenom Pro) equipped with an energy dispersive spectrometer (EDS) was used to characterize the composition of the single crystalline CsAg2I3 thermal insulation material.

[0070] (III) Determination and calculation of thermal conductivity:

[0071] For the temperature range of 220K to 390K, the thermal conductivity (κ) was measured by the laser flash method (Netzsch LFA467, Germany), that is, κ = ρC p λ, where ρ is the density, C p is the heat capacity (the Duron-Pettit heat capacity limit is used in this application), and λ is the thermal diffusivity measured directly by the instrument. All samples had a thickness of 0.7-1 mm and were tested in an argon environment. For the temperature range from 4 K to 120 K, the steady-state method (Multifield Technologies) was used to measure the thermal conductivity as κ = PL / (ΔTS), where P is the heater power, L is the length between the two thermocouple contacts, ΔT is the temperature difference after heating stabilizes and before heating, and S is the cross-sectional area of ​​the sample. All measurements were performed at less than 10 -5 The test was carried out under high vacuum conditions of 1.5×3.5×4 mm. 3 .

[0072] (IV) Three-dimensional synchrotron X-ray diffuse scattering measurement:

[0073] Three-dimensional synchrotron X-ray diffuse scattering measurements were performed at the QM2 beamline of the Cornell High Energy Synchrotron Light Source (CHESS). Single crystalline CsAg2I3 insulators were measured at 300K using an incident beam energy of 50.0keV. A PILATUS 6M CdTe 2D detector was mounted behind the sample, perpendicular to the main beam path, with a sample-to-detector distance of 400.63 mm. During the measurement, the sample was continuously rotated 365° around an axis perpendicular to the beam at a speed of 1° per second, and images were read out every 0.1 seconds. Three sets of rotational images were collected for the single crystalline CsAg2I3 insulator sample to fill the detector gap and eliminate detector artifacts. The resulting images were stacked into a three-dimensional array and transformed into reciprocal space coordinates using NXRefine and CCTW (Crystal Coordinate Transformation Workflow) software packages in NeXpy3. The resulting structure function S(Q) has a range of ±27, ±16, and ±16 in the H, K, and L reciprocal lattice directions, respectively.

[0074] (V) Speed ​​of sound:

[0075] The sound velocities in three directions of the single-crystalline CsAg2I3 insulating material were measured at room temperature by an ultrasonic pulse receiver (Olympus-NDT) equipped with an oscilloscope (Keysight).

[0076] (VI) Raman spectroscopy:

[0077] Room temperature Raman spectroscopy of the polycrystalline CsAg2I3 adiabatic material was performed by a LABRAM HR-EVOLUTION Raman spectrometer (HORIBA) with an excitation laser wavelength of 532 nm and equipped with an ultra-low frequency filter to observe low-frequency Raman active modes.

[0078] (VII) Archimedean method for measuring density

[0079] The Archimedean method is a displacement method, which measures the change in the scale before and after the material is immersed in the measuring cylinder. The displacement volume difference is the volume of the material. The density of the material can be calculated based on the volume and the mass of the material.

[0080] Experimental results:

[0081] Figure 1 In the figure, the X-ray diffraction pattern of the polycrystalline CsAg2I3 thermal insulation material powder changing with temperature is shown in Figure (a); the lattice parameters of the polycrystalline CsAg2I3 thermal insulation material powder changing with temperature is shown in Figure (b). During the process of heating from room temperature 300K to 410K, the XRD diffraction pattern of the polycrystalline CsAg2I3 thermal insulation material did not change, indicating that its phase did not change with temperature; the X-ray diffraction pattern of the (100) / (010) / (001) plane of the CsAg2I3 single crystal is shown in Figure (c); the SEM and EDS images of the surface of the CsAg2I3 single crystal are shown in Figure (d). According to the element distribution map given by the energy dispersive spectrometer, it is confirmed that the three elements Cs / Ag / I are evenly distributed and there are no other impurity elements, which proves that the single crystalline CsAg2I3 thermal insulation material has high phase purity and uniform phase composition.

[0082] The relationship between the thermal conductivity (κ) and temperature of polycrystalline CsAg2I3 and single crystal CsAg2I3 with different crystal axis orientations is shown in the figure Figure 2As shown; it can be seen from the figure that the thermal conductivity of CsAg2I3 is below 0.3W / mK in the entire temperature range, and the thermal conductivity of the a-axis oriented single crystal has a peak near 30K, proving that the material is crystalline. The thermal conductivity above 30K decreases with increasing temperature, revealing that its thermal transport performance is mainly phonon conduction. The thermal conductivity of polycrystalline CsAg2I3 at room temperature is 0.09W / mK, indicating that it has excellent thermal insulation properties. At 300K, when the single crystal orientation is a-axis, the thermal conductivity of the insulating material is 0.08W / mK; when the single crystal orientation is b-axis, the thermal conductivity of the insulating material is 0.15W / mK; when the single crystal orientation is c-axis, the thermal conductivity of the insulating material is 0.14W / mK; it can be seen that when the single crystal orientation is a-axis, the thermal conductivity is the lowest and the thermal insulation performance is the best.

[0083] The three-dimensional X-ray diffuse scattering stacking diagram of single-crystalline CsAg2I3 thermal insulation material at room temperature on the Q=(HKL) plane is shown in the figure below. Figure 3 (a) shows that the data were converted into reciprocal space coordinates using the CCTW (Crystal Coordinate Transformation Workflow) software package. The diffusion line pattern in the reciprocal space of the direction of the diffusion signal indicates that there is a local structural disorder along a specific direction. The diffusion signal corresponds to the positive space along (101) and The atomic displacement in the direction normal to the plane. Figure 3 As shown in (b), the mean square displacement of each atom in the three crystal axis directions calculated based on single crystal X-ray diffraction refinement and AIMD simulation shows that the atomic vibration displacement of Cs atoms, I2 atoms and I3 atoms in the a and c directions is significantly greater than that in the b direction, which is consistent with the positive space along (101) and The anisotropic atomic vibration mode that only exists in the ac plane is the main reason for the anisotropy of thermal conductivity of CsAg2I3 insulating material.

[0084] The transverse and longitudinal sound velocities and Raman spectra of CsAg2I3 insulation material measured along different crystal axes at room temperature are shown in Figure 2. Figure 4 (a) and (b). This atomic vibration mode that only exists on the ac plane corresponds to an ultra-low frequency optical phonon branch, which can be observed in the Raman spectrum. This ultra-low frequency optical branch causes the acoustic phonon velocity to decrease, and the anisotropy of atomic vibration leads to anisotropy in phonon transport behavior, one of the manifestations of which is the anisotropy of the phonon group velocity.

[0085] The density of the polycrystalline and single-crystalline cesium silver iodine thermal insulation materials described in Examples 1 and 2 is about 5.0-5.1 g / cm2 as measured by the Archimedean method. 3 According to the lattice structure information, the theoretical density is calculated to be 5.11 g / cm3 The density of polycrystalline and single-crystalline cesium silver iodine insulation materials is above 97%.

[0086] In summary, the present invention is excellent in material density and thermal insulation performance, and has great potential for application in thermal insulation and energy-saving materials.

[0087] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A cesium silver iodine insulation material with ultra-low thermal conductivity, characterized in that: Its chemical formula is CsAg2I3; the cesium silver iodine thermal insulation material includes polycrystalline cesium silver iodine thermal insulation material and single crystal cesium silver iodine thermal insulation material; the density of the cesium silver iodine thermal insulation material is 4.6-5.1g / cm 3 , the density is 90~100%.

2. A method for preparing a polycrystalline cesium silver iodine thermal insulation material, characterized in that: The following steps are involved: (1) Vacuum packaging: the raw materials cesium iodide CsI and silver iodide AgI are mixed evenly and then vacuum packaged in a quartz tube; (2) Melt reaction quenching: The quartz tube is heated to allow the raw materials to react in a molten state, and then the furnace is stopped and cooled to a certain temperature, and then quenched and cooled to obtain the first ingot; (3) Heat treatment and quenching: the first ingot is vacuum-sealed in a quartz tube, heat-treated, and then quenched and cooled to obtain a second ingot; (4) Pressure sintering: The second ingot is ground into powder, placed in a mold, and subjected to vacuum high-temperature hot-pressing sintering. The dense block material obtained after cooling is the polycrystalline cesium silver iodine thermal insulation material.

3. The method for preparing a polycrystalline cesium silver iodine thermal insulation material according to claim 2, characterized in that: The molar ratio of the raw materials cesium iodide CsI and silver iodide AgI in step (1) is 1:2; the purity of the raw materials is greater than 99.9%; the absolute vacuum degree of the vacuum in step (1), step (3) or step (4) is not greater than 10 -1 Pa; the heating in step (2) is: heating the quartz tube from room temperature to 973-1173K at a rate of 140-180K / h and keeping it warm for 1-3h, so that the raw materials react in a molten state; the shutdown cooling is: cooling the quartz tube from 973-1173K to 523-723K at a rate of 100-120K / h.

4. The method for preparing a polycrystalline cesium silver iodine thermal insulation material according to claim 2, characterized in that: The heat treatment in step (3) is as follows: heating the quartz tube from room temperature to 373-473K at a rate of 40-80K / h and keeping the temperature for 1-3 days.

5. The method for preparing a polycrystalline cesium silver iodine thermal insulation material according to claim 2, characterized in that: In step (4), the vacuum high-temperature hot pressing sintering is carried out by heating the temperature to 373-423K at a rate of 40-60K / min, adjusting the pressure to 40-50MPa, and maintaining the temperature and pressure for 5-15min; the cooling rate is 5-15K / min.

6. A method for preparing a single-crystalline cesium silver iodine thermal insulation material, characterized in that: The following steps are involved: (1) Vacuum packaging: the raw materials cesium iodide CsI and silver iodide AgI are mixed evenly and then vacuum packaged in a quartz tube; (2) Melting reaction furnace cooling: The quartz tube is heated to allow the raw materials to react in a molten state, and then the furnace is stopped and cooled to obtain a polycrystalline first ingot; (3) Single crystal growth: vacuum-packing the first polycrystalline ingot in a quartz tube, placing the quartz tube in a furnace and heating it, cooling it to room temperature after it is completely melted, so that the compound solidifies and crystallizes from the molten state, thereby obtaining the single crystal cesium silver iodine thermal insulation material.

7. The method for preparing a single-crystalline cesium silver iodine thermal insulation material according to claim 6, characterized in that: The molar ratio of the raw materials cesium iodide CsI and silver iodide AgI in step (1) is 1:2; the purity of the raw materials is greater than 99.9%; the absolute vacuum degree of the vacuum in step (1) or step (3) is not greater than 10 -1 Pa.

8. The method for preparing a single-crystalline cesium silver iodine thermal insulation material according to claim 6, characterized in that: The heating in step (2) is: heating the quartz tube from room temperature to 973-1173K at a rate of 140-180K / h and keeping it warm for 1-3h, so that the raw materials react in a molten state; the shutdown cooling is: cooling the quartz tube from 973-1173K to room temperature at a rate of 100-120K / h.

9. The method for preparing a single-crystalline cesium silver iodine thermal insulation material according to claim 6, characterized in that: The heating in step (3) is controlled by the tip of the quartz tube, and the temperature is raised from room temperature to 453-513K at a rate of 40-80K / h and kept at this temperature for 1-3h; the cooling is: lowered to room temperature at a rate of 0.5-1K / h.

10. The use of a cesium silver iodine insulation material with ultra-low thermal conductivity as claimed in claim 1, characterized in that: The cesium silver iodine thermal insulation material with ultra-low thermal conductivity is used to prepare thermal shielding covers for experimental equipment, building insulation materials or thermal insulation and protective products for daily use.

Citation Information

Cited By

  • Cs3Bi2I9 single-crystal material with double heat transfer operation modes as well as preparation method and application of Cs3Bi2I9 single-crystal material

    CN121006598A